KONDISI SOSIAL EKONOMI KELUARGA PETANI CACAO DI KENAGARIAN SIKUCUR KECAMATAN V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Yulmaita, Yulmaita; Juita, Erna; Zuriyani, Elvi (STKIP PGRI Sumbar, 2013)
This study aimed to obtain information on data on Socio-Economic Condition Family Farmers Cacao In Kenagarian Sikucur District V Koto Kampung Dalam. Discuss about 1) the state of education in the whole family Kenagarian Sikucur cacao farmers, 2) the condition of cacao farm family income, 3) cacao farmers work conditions, and 4) the condition of ownership of family assets cacao farmers in Kenagarian Sikucur In District V Koto Kampung Padang Pariaman district .Classified research on descriptive research, family research subject is that cacao farmers in Kenagarian Sikucur. Kenagarian Sikucur consisting of fourteen surroundings. The sampling technique used is the sample of respondents. the number of respondents in this study was 104 households. Data collection techniques used were interviews and observation, data collection tools by using a questionnaire study. Techniques of data analysis is descriptive in the form of a percentage formula. Results of this study include : 1) the state of education cacao farmers in general not just at the level of junior high school - graduate (74 %) and upper middle as many (72.9 %), 2) The condition of high category cacao farmers income is Rp. > 1,000 .000-1.250.000 (65.3 %) and Rp. > 1,250,000 (30.7 %) , 3) Conditions before farming cacao farmers work in general farming and coconut rice (75.8 %), with a side jo b trade and the self-employed (82.6 %), 4 ) the condition of assets cacao farmers in general have two vehicles per household (58.6 %), type of house most of the permanent farmers (84.6 %) homes (53.8 %) and the status of the land or land planted in cacao are generally owned their own (73.0 %) .